MENGUKUR TINGKAT KESEHATAN KEUANGAN PT WIJAYA KARYA (PERSERO) TBK. BERDASARKAN KEPUTUSAN MENTRI BUMN NO KEP-100/MBU/2002 - Hamizar, Hamizar (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to measure the financial performance of PT Wijaya Karya (Persero) Tbk during the 2021–2023 period using financial ratio analysis as an evaluation tool. Secondary data obtained from annual financial reports was used to calculate and analyze various ratios, including liquidity, solvency, profitability, and activity ratios. The methodology applied included calculating the cash ratio, net profit margin, return on assets, and other ratios to provide a comprehensive overview of asset management efficiency and the company's ability to meet short-term obligations. The results of the study indicate a downward trend in several performance indicators, particularly profitability and liquidity, reflecting operational pressures in 2023 compared to the previous period. These findings provide a comprehensive overview of the company's financial condition and indicate the need for adjustments to its financial management strategy to improve stability and competitiveness in the future.